Binge-like sucrose consumption reduces the dendritic length and complexity of principal neurons in the adolescent rat basolateral amygdala. - Masroor Shariff; Paul Klenowski; Michael Morgan; Omkar Patkar; Erica Mu; Mark Bellingham; Arnauld Belmer; Selena E Bartlett (PLoS ONE)
A compelling body of evidence suggests that the worldwide obesity epidemic is underpinned by excessive sugar consumption, typified by the modern western diet. Furthermore, evidence is beginning to emerge of maladaptive changes in the mesolimbic reward pathway of the brain in relation to excess sugar consumption that highlights the importance of examining this neural circuitry in an attempt to understand and subsequently mitigate the associated morbidities with obesity. While the basolateral amygdala (BLA) has been shown to mediate the reinforcing properties of drugs of abuse, it has also been shown to play an important role in affective and motivated behaviours and has been shown to undergo maladaptive changes in response to drugs of abuse and stress. Given the overlap in neural circuitry affected by drugs of abuse and sucrose, we sought to examine the effect of short- and long-term binge-like sucrose consumption on the morphology of the BLA principal neurons using an intermittent-access two-bottle choice paradigm. We used Golgi-Cox staining to impregnate principal neurons from the BLA of short- (4 week) and long-term (12 week) sucrose consuming adolescent rats and compared these to age-matched water controls. Our results indicate possibly maladaptive changes to the dendritic architecture of BLA principal neurons, particularly on apical dendrites following long-term sucrose consumption. Specifically, our results show reduced total dendritic arbor length of BLA principal neurons following short- and long-term sucrose consumption. Additionally, we found that long-term binge-like sucrose consumption caused a significant reduction in the length and complexity of apical dendrites. Taken together, our results highlight the differences between short- and long-term binge-like sucrose consumption on BLA principal neuron morphology and are suggestive of a perturbation in the diverse synaptic inputs to these neurons.